Effect of Cyclodextrins Formulated in Liposomes and Gold and Selenium Nanoparticles on siRNA Stability in Cell Culture Medium - Betzaida Castillo Cruz; Sandra Chinapen Barletta; Bryan G. Ortiz Muñoz; Adriana S. Benitez-Reyes; Omar A. Amalbert Perez; Alexander C. Cardona Amador; Pablo E. Vivas-Mejia; Gabriel L. Barletta (MDPI AG, 2024)
Background: Encapsulation of siRNA fragments inside liposome vesicles has emerged as an effective method for delivering siRNAs in vitro and in vivo. However, the liposome's fluid-phospholipid bilayer of liposomes allows siRNA fragments to diffuse out of the liposome, decreasing the dose concentration and therefore the effectiveness of the carrier. We have previously reported that β-cyclodextrins formulated in liposomes help increase the stability of siRNAs in cell culture medium. Here, we continued that study to include α, γ, methyl-β-cyclodextrins and β-cyclodextrin-modified gold and selenium nanoparticles. Methods: We used Isothermal Titration Calorimetry to study the binding thermodynamics of siRNAs to the cyclodextrin-modified nanoparticles and to screen for the best adamantane derivative to modify the siRNA fragments, and we used gel electrophoresis to study the stabilization effect of siRNA by cyclodextrins and the nanoparticles. Results: We found that only β- and methyl-β-cyclodextrins increased siRNA serum stability. Cyclodextrin-modified selenium nanoparticles also stabilize siRNA fragments in serum, and siRNAs chemically modified with an adamantane moiety (which forms inclusion complexes with the cyclodextrin-modified-nanoparticles) show a strong stabilization effect. Conclusions: β-cyclodextrins are good additives to stabilize siRNA in cell culture medium, and the thermodynamic data we generated of the interaction between cyclodextrins and adamantane analogs (widely used in drug delivery studies), should serve as a guide for future studies where cyclodextrins are sought for the delivery and solvation of small organic molecules.